Bromocriptine therapy: Review of mechanism of action, safety and tolerability. (22nd June 2022) - Naz, Faiza; Malik, Abdul; Riaz, Muhammad; Mahmood, Qaisar; Mehmood, Malik Hassan; Rasool, Ghulam; Mahmood, Zahed; Abbas, Mazhar
Abstract: Bromocriptine is a sympatholytic dopamine D2 receptor agonist with remarkable bioactivities. It has been used clinically as a prescription drug for more than 30 years to treat hyperprolactinemia associated conditions, Parkinson's disease, acromegaly, prolactinomas and other pituitary hormone dependent adenomas and recently, diabetes mellitus as well as various other disorders. Long‐term treatment with bromocriptine has minimal or no harmful effects on renal, hepatic, cardiac or hematologic functions. This review article was planned to study the hypothetical and proposed mechanism of action as well as provide a brief discussion about its safety issues and tolerability. Bromocriptine represents an attractive option with high efficacy and safety profile for hyperprolactinemia‐associated conditions, acromegaly, parkinsonism, type 2 diabetes mellitus and various other diseases in a variety of dosage forms for best possible beneficial effects. It appeared to be an effective and safe addition to the pharmacopoeia of drugs for the treatment of a vast variety of diseases as monotherapy or in combination with other drugs. Abstract : Thematic of bromocriptine's therapy mechanism of actions